Fruit yield of jalapeno pepper with worm leachate and two irrigation methods. - Maraña Santacruz, José Ángel; Castellanos Pérez, Edmundo; Vázquez Vázquez, Cirilo; Martínez Ríos, Juan José; Trejo Escareño, Héctor Idilio; Gallegos Robles, Miguel Ángel; Orona Castillo, Ignacio (REVISTA TERRA LATINOAMERICANA, 2018)
Worm leachate and water use eff iciency are important factors in food production. The objective of the study was to evaluate the response of jalapeño pepper (Capsicum annuum) to two doses of worm leachate under two irrigation methods and some soil chemical variables. This study was conducted at the Facultad de Agricultura y Zootecnia de la UJED, Mexico, in 2013 and 2014. The experimental design was split-plots randomly distributed with four replications. The main plot was irrigation method, drip irrigation at 60% of the evaporation (EV) and surface irrigation at 80% EV. The subplot was fertilization at 2400 and 4800 L ha-1 worm leachate (worm Tea). The drip irrigation treatment had higher fruit yield than surface irrigation in both years (P < 0.05). Fruit yield of the worm leachate treatment of 4800 L ha-1 was similar to the 2400 L ha-1 treatment in 2013 but was higher in 2014 (P < 0.05). Organic matter in the irrigation factor was signif icantly different in soil depth of 0-30 cm: drip irrigation treatment with 1.61% vs 1.43% in superf icial irrigation in 2014 (P < 0.05). Also, pH and electrical conductivity (EC) had higher values in the drip irrigation treatment at soil depth of 0-30 cm in 2014 (P < 0.05). Drip irrigated plots were watered with 60% of the amount of evaporation for a total of 60 cm in 2013 and 51 cm in 2014. Surface water irrigated was applied to complete 80% of the evaporation for a total of 78 cm of water in 2013 and 63 cm in 2014. The worm leachate with drip irrigation reduced evaporation, with a water savings of 15.22%, and the higher frequency of irrigation in the root area of the plant produced higher yield.